Mathematical modeling for stabilized plate controlling - Srisumoungklounggoon, Totsapon (RMUTSB ACADEMIC JOURNAL, 2023)
The stabilized plate is a device designed for various applications with high safety requiring, involving the movement of delicate and fragile items in hospital to keep patients position stable to prevent potential harm or danger. This research introduces the design of a stabilized plate control system using a Linear Quadratic Regulator (LQR) control scheme. The mathematical model was constructed using Lagrange,s equation to aid in calculations. MATLAB/Simulink software was then used to create a motion model for the stabilized plate. Real-world experiments were conducted using an acceleration sensor to measure the tilt angle of the stabilized plate. MATLAB/Simulink was also employed to control the stabilized plate’s position. Simulation results showed that the system took approximately 1 second to reach the equilibrium position, which was the balance state of the system. In real-world experiments, it was observed that the designed control system can maintain the balance of plate within approximately 2 seconds when the plate became tilted.